Nonlinear Modeling of MGSPMs Based on Hybrid Subdomain and Magnetic Equivalent Circuitry - Dianati, Babak; Hahn, Ingo (IEEE Transactions on Magnetics, 2022)
The need for combining two mechanical powers with electrical power is a vital part of many applications, such as hybrid electric vehicles. The magnetic geared surface permanent magnet (MGSPM) motor is a compact and efficient way of achieving this goal. However, their complex structure demands time-consuming optimizations, which requires a large number of simulations. In this context, a fast and accurate simulation method is required to reduce the design and optimization time. In addition to speed and accuracy in considering the complex structures of the machine, as the saturation effect has a major impact on the accuracy of the simulations in these machines, it must be included in the method. To tackle this problem, in this article, a hybrid subdomain (SD) and magnetic equivalent circuit (MEC) model is proposed, considering the saturation effect of the iron parts using current distributions in the SD model on the surfaces of modulators and rotor core, as well as in the stator slots. These currents are calculated using the MEC model of the respective parts and Ampere's law. Furthermore, an example motor is simulated both using the proposed method and the FE method, and the accuracy of the method both for prediction of magnetic flux density inside iron parts and prediction of flux linkages of the machine for a variety of designs and excitations is verified.
CRIS-Team WoS Importer:2021-12-31